Physiological, biochemical, and metabolic changes in diploid and triploid watermelon leaves during flooding - He, Nan; Umer, Muhammad Jawad; Yuan, Pingli; Wang, Weiwei; Zhu, Hongju; Lu, Xuqiang; xing, Yan; Gong, Chengsheng; Batool, Raufa; Sun, Xiaowu; Liu, Wenge (Frontiers in Plant Science, 2023)
Flooding is a major stress factor impacting watermelon growth and production globally. Metabolites play a crucial role in coping with both biotic and abiotic stresses. In this study, diploid (2X) and triploid (3X) watermelons were investigated to determine their flooding tolerance mechanisms by examining physiological, biochemical, and metabolic changes at different timepoints. The results showed that 2X watermelon leaves had lower chlorophyll content and fresh weights in shoots and roots compared to 3X. The activities of antioxidants, such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), were higher in 3X than in 2X. 3X watermelon leaves showed lower O2 production rates, MDA, and hydrogen peroxide (H2O2) levels in response to flooding, while higher ethylene production was observed. 3X had higher levels of dehydrogenase activity (DHA) and ascorbic acid + dehydrogenase (AsA + DHA), but both 2X and 3X showed a significant decline in the AsA/DHA ratio at later stages of flooding. Metabolite quantification was done using UPLC-ESI-MS/MS and a total of 682 metabolites were detected. Among them, 4-guanidinobutyric acid (mws0567), an organic acid, may be a candidate metabolite responsible for flooding tolerance in watermelon and had higher expression levels in 3X watermelon, suggesting that triploid watermelon is more tolerant to flooding. This study provides insights into the response of 2X and 3X watermelon to flooding and the physiological, biochemical, and metabolic changes involved. It will serve as a foundation for future in-depth molecular and genetic studies on flooding response in watermelon.